Exact low-order polynomial expressions to compute the Kolmogoroff–Nagumo mean in the affine symplectic group of optical transference matrices. Issue 4 (3rd April 2017) - Fiori, Simone; Prifti, Stilian
Abstract : The current contribution presents exact third-order polynomial expressions of matrix functions that arise in the computation of the Kolmogoroff–Nagumo mean of a set of optical transference matrices, that belong to the affine symplectic group .